Evaluation of different haematoxylin stain subtypes for the optimal microscopic interpretation of cutaneous malignancy in Mohs frozen section histological procedure. Issue 2 (3rd April 2021) - Gabriel, JA; Shams, M; Orchard, GE
ABSTRACT: Background: The Mohs technique employs mainly H&E-stained frozen sections for surgical margin assessment of cutaneous excisions, utilising microscopic evaluation of the complete, circumferential, peripheral and deep margins. This study aimed to determine which mordant based haematoxylin (Ehrlich's, Cole's, Mayer's, Gill's I, Gill's II, Gill's III, Weigert's, Harris' or Carazzi's) produced the optimal morphological clarity of staining for the identification of cellular and tissue morphology of cutaneous basal cell carcinoma (BCC). Material and methods: In total, 100 anonymised patient cases were selected, sectioned and stained with each haematoxylin subtype. The slides were independently evaluated microscopically by two assessors. A combined score was generated to determine the sensitivity (defined as the intensity of haematoxylin staining being too weak or too strong and the colour appearance of the haematoxylin not being blue/black) and specificity (defined as the appearance of background staining with haematoxylin, uneven staining and staining deposits) for each of the nine haematoxylin subtypes. The scoring criteria were based on the UKNEQAS CPT Mohs procedure assessment criteria. Results: The scores generated for specificity identified Carazzi's haematoxylin as best performing (99.2%) followed by Gill's III (98.4%), Ehrlich's (98.2%) and Harris' (85.0%). The sensitivity score again identified Carazzi's as producing the best result (85.0%) followed by Weigert's (83.4%), Ehrlich's (81.6%) and Gill's III (80.4%). Discussion: Carazzi's haematoxylin is the most optimal staining dye for the identification of BCC tumour for use as part of the Mohs micrographic surgery procedure.